Promosi Kesehatan tentang Anemia pada Ibu Hamil di Wilayah Kerja Puskesmas Pabelan, Kabupaten Semarang - Ana Mufidaturrosida; Farida Utaminingtyas; Diyan Indah Sri Ambarwati; Nining Faizah Hanum; Fadhilatul Islamiyah (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
Anemia in pregnant women is a medical condition characterized by low hemoglobin levels in the blood, reducing the blood’s ability to transport oxygen to body tissues. In pregnant women, anemia can cause decreased immunity, dizziness, shortness of breath, and the risk of bleeding during childbirth. In the fetus, anemia can cause intrauterine growth retardation, low birth weight (LBW), premature birth, and even long-term cognitive developmental disorders. Health education and promotion are needed to increase pregnant women’s knowledge and awareness of the importance of anemia prevention. The goal of this activity is to increase pregnant women’s understanding of anemia and its prevention in order to reduce morbidity and mortality in pregnant women and their fetuses. This activity method is implemented by delivering material followed by a discussion and question-and-answer session. Evaluation results indicate an increase in pregnant women’s understanding of anemia and its prevention.